Treatment of Hypertension in Black Patients With Angiotensin-Converting Enzyme Inhibitors - Shulman, Neil B. (1988)
The prevalence of hypertension and the incidence of complications from uncontrolled elevated blood pressure in blacks is much greater than in the white population. In general, blacks have underlying differences in the factors relating to blood pressure level, including low plasma renin, and, in certain instances, a decreased ability to excrete sodium. The stepped-care approach in the management of the black hypertensive patient is similar to that taken with white patients, but racial differences in response to antihypertensive drugs exist that require careful consideration when choosing a treatment regimen. Thiazide diuretics are effective in blacks and are often used as initial therapy. Blacks tend to respond less well to β-blockers, but when combined with a diuretic, they are also effective. Encouraging data are available on the use of calcium channel blockers in blacks. When combined with a diuretic, the angiotensin-converting enzyme (ACE) inhibitors also provide an alternative to therapy for black patients. The use of low doses of ACE inhibitors has reduced the high incidence of adverse effects associated with this group of drugs in earlier studies.